How Does the Exchange Rate Affect the Real Economy? A Literature Survey - Enzo Cassino; David Oxley (New Zealand Government, The Treasury, 2013)
We examine the relationship between exchange rate movements and the real economy – an area that has been the focus of considerable debate in recent years. We consider different concepts of exchange rate equilibrium, and review recent evidence on whether the New Zealand dollar exchange rate reflects its fundamental determinants. We also review the theoretical and empirical evidence on the relationship between movements in the exchange rate and the resulting impacts on the wider economy. We conclude that the nature of the relationship between the movements in the exchange rate and the resulting adjustment in the real economy depends on the nature of the shocks that affect the economy. This has important policy implications as policymakers need to have a clear understanding of the nature of the shock when deciding on appropriate responses. In practice, however, it is often difficult for policymakers to identify accurately the types of shocks hitting the economy, especially in real time. While the New Zealand dollar exchange rate may be overvalued at present, the equilibrium value of the exchange rate may also have risen, possibly due to higher export commodity prices. Tradable sector output growth has declined since the mid-2000s, but within the tradable sector, activity in resource-based industries has risen strongly, while manufacturing output and exports of services has declined. This is consistent with "Dutch disease" effects, as higher commodity prices lead to a crowding out of non-commodity exports. Sensitivity to exchange rate movements also varies across New Zealand's economic sectors and industries. The agricultural sector is relatively insensitive to exchange rate movements, while the manufacturing and service sectors are more vulnerable.
Keywords: F31; F41; F43; 330; Exchange Rate Valuation; Fundamentals; Equilibrium; Economic Growth; Dutch Disease